Molecular diagnosis of Trichomonas vaginalis in liquid-based Papanicolaou samples in Shiraz, southern Iran - Mohammad Saleh Bahreini; Samaneh Sedghi; Yalda Badalzadeh; Mohammad Hossein Motazedian; Manouchehr Shirani; Sareh Sami Jahromi; Aref Teimouri; Mahmoud Agholi; Qasem Asgari (BMC, 2023)
Abstract Background Trichomoniasis is a parasitic infection of the urinary and genital tract, caused by Trichomonas vaginalis. This study aimed to investigate the molecular diagnosis of T. vaginalis infection in liquid-based Papanicolaou samples in Shiraz, southern Iran. Materials and methods In this cross-sectional study, 534 liquid-based Papanicolaou samples were collected from women referring to the laboratory of Motahari Clinic of Shiraz University of Medical Sciences in 2021. Genomic DNA were extracted from the samples and examined for evidence of T. vaginalis using polymerase chain reaction (PCR) using TVK3 and TVK7 specific primers. Results The mean age of participants was 39.28 ± 9.89 with a maximum age of 65 and a minimum age of 19 years. T. vaginalis DNA fragments were detected in 4.86% (26/534) of the cases. There was significantly higher prevalence in the age groups of 21 to 30 and 41 to 50 years (46.15%, p = 0.001 and 38.46%, p = 0.015, respectively). Furthermore, the results showed an association between a history of foamy discharge and Trichomonas positivity (p = 0.001). Conclusion T. vaginalis infection is common in liquid-based Papanicolaou samples of women who attended regular health check-ups in the study area. Screening for trichomoniasis in populations, particularly if using highly sensitive methods such as PCR, may lead to increased detection and treatment.